Cost drivers for benign hysterectomy within a health care system: Influence of patient, perioperative, and hospital factors. Issue 2 (14th December 2022) - Kohn, Jaden R.; Frost, Anja S.; Tambovtseva, Anastasia; Hunt, Megan; Clark, Katharine; Wilson, Christina; Borahay, Mostafa A.
Abstract: Objective: To identify patient, perioperative, and hospital factors that drive total hospital charges for benign hysterectomy. Methods: The authors conducted a retrospective cohort study between July 2014 and February 2019 at five academic and community hospitals within an integrated healthcare system in the state of Maryland with a Global Budget Revenue methodology for hospital charges. Predictor variables included patient, perioperative and hospital characteristics. One‐way analysis of variance was used to compare charges among approaches. A multiple linear regression model was built to account for the interaction between covariates. Results: A total of 2592 patients underwent hysterectomy via laparoscopic (61%), abdominal (16%), robotic (14%), or vaginal (9%) approaches. Before adjusting for covariates, laparoscopic and vaginal approaches had similar charges ($11 637 and $12 229, respectively), while robotic and open approaches had higher charges ($17 535 and $19 099, respectively). After adjusting, charges for open, laparoscopic, and robotic approaches were higher than the vaginal approach ($692, $712, and $1279, respectively). Each operating room minute resulted in an increased cost of $46. Length of stay >23 h was associated with an increase of $865. Year, uterine size, body mass index, additional procedures, and transfusion influenced charges. Conclusion: Perioperative and hospital characteristics significantly influence hospital charges for benign hysterectomy, more so than nonmodifiable patient characteristics. This provides opportunities to reduce healthcare expenditures, such as improving operating room efficiency and reducing length of stay. Synopsis: Benign hysterectomy hospital charges are mostly influenced by perioperative and hospital characteristics, rather than patient characteristics.